An Evaluation of the Performance of Exotic Pines at New forest - Dwivedi, A. P.; Thapar, H. S. (Indian Forester, 1990)
The paper gives an appraisal of the growth performance of different species and origins of exotic pines raised at New Forest, F.R.I., Dehra Dun in different trails. Among species Pinus caribaea was found to be the best performer as far as height and diameter growth is concerned followed by Pinus elliottii. The highest survival was observed in Pinus elliottii and lowest in Pinus oocarpa. A spacing of 2.5 X 2.5 m and beyond indicated best diameter growth in P.caribaea var. babamensis. Among Caribaaes, Pinus caribaea var. hondurensis provanances from Poptun Peten Guatemala, Alamicamba. Nicaragua and for P.caribaea var. bahamensis provanance from Andros Island performed better in comparison to otbers; No significant difference was found in any of the parameters studied among the different provenances of Pinus oocarpa.